Determinanten und Perspektiven des Verkehrsverhaltens. USA und Deutschland im Vergleich. - Bühler, Ralph; Kunert, Uwe (Deutscher Verkehrs-Verl., 2010)
In einer Kooperation der Rutgers University (New Jersey) und des DIW Berlin wurde untersucht, auf welche Faktoren Unterschiede und Gemeinsamkeiten in der Mobilität zurückzuführen sind und ob die Trends für beide Länder in eine gemeinsame Richtung weisen.

The article explores the role of socioeconomic and demographic factors, spatial development patterns, and transport policies as explanatory factors for dissimilar travel behaviour in Germany and the USA. We find that all groups of society in the USA are more car dependent than Germans - even after controlling for socioeconomic factors and spatial development patterns. For example, Americans living in the highest population density category still travel more kilometres by car per day than Germans in the lowest population density category. Similarly, Germans in the highest income quartile drive fewer kilometres by car per day than Americans in the lowest income quartile. A multivariate analysis shows that transport policy proxy variables capture up to 25 % of the explained variability. We also find that car travel distance in the USA is more sensitive to automobile operating costs: a 10 % increase in automobile operating cost per m is associated with a 2 % reduction in car travel distance in the USA, comparedto only 1.6 % in Germany. The price sensitivity of car travel in the USA is demonstrated by an analysis of the decline in vehicle kilometres of car travel over the last two years.
Determinants and outlook on travel behaviour in Germany and the USA.
Keywords: Individualverkehr; Verkehrspolitik; Mobilität; Personenkraftwagen; Autoverkehr; Verkehrsnachfrage; Verkehrsaufkommen; Verkehrsprognose; Verkehrsstatistik; Verkehrsverhalten; Verkehrsmittelwahl; Distanz; Raumaufteilung; Internationaler Vergleich; Mobilitätskosten; Kraftstoffverbrauch; Sozioökonomie; Alltagsverkehr